Different Understandings of Scientific Research in the Use of De-identified Personal Sensitive Data: South Korea, in Comparative Perspectives - You, Jong Sung; Kim, Jaiyong (International Journal of Population Data Science, 2026)
There have been conflicts between the private sector and civil society surrounding the secondary use of administrative data in South Korea. In particular, the actual loss insurance industry has strongly requested access to the administrative data on health care records and demographic and socioeconomic information compiled by the National Health Insurance Service. Public opinion is generally unfavorable toward providing the private sector with sensitive personal data even in a de-identified form. Korea’s Personal Information Protection Act states that de-identified data can be used for the purpose of scientific research. However, the definition of scientific research is understood differently, particularly whether the private sector’s research and development should be regarded as scientific research. We examine the conflicts surrounding this issue, including the positions of various stakeholders and the public opinion in South Korea. We compare the legal provisions and public discourse in South Korea with those in several other countries, including the U.S., U.K., EU, Finland, and Australia. In particular, we explore if the distinction between “scientific research” and “development and innovation activities” and strict prohibition of use of health data for marketing and insurance purposes in Finland can be an acceptable model in South Korea.